2010
DOI: 10.1258/ijsa.2009.008514
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a school-based HIV/AIDS peer-led prevention programme: the first intervention trial for children of migrant workers in China

Abstract: The effectiveness of a peer-led education intervention in HIV/AIDS prevention was assessed in the Chinese children of migrant workers. A prospective study was conducted in 12 junior high schools for migrant children. Among the intervention group, a peer-education-based HIV/AIDS prevention was implemented for three months. The results during the baseline survey indicated that the level of knowledge on HIV/AIDS was lower in children of migrant workers. After three months of peer-led intervention, compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Women often work in the service industry and may even provide paid sexual services as sex workers. Some previous studies suggested that migrants have contributed to the HIV/AIDS epidemic [4][7].…”
Section: Introductionmentioning
confidence: 99%
“…Women often work in the service industry and may even provide paid sexual services as sex workers. Some previous studies suggested that migrants have contributed to the HIV/AIDS epidemic [4][7].…”
Section: Introductionmentioning
confidence: 99%
“…Although a substantial number of the reviewed studies converge on the positive impact of education/enlightenment campaigns on prevention programs, there are few divergent views on the most effective method. While Li et al (2010), observed that in programs attempting to bring about behavior change among adolescents, peer-led health education has been demonstrated to be an effective method of programme delivery. Studies conducted by Wakefield, Loken, & Hornik (2010) and Anema et al (2010) considered media campaigns as the best way to educate young people about the disease and condom use.…”
Section: The Influence Of Hiv-aids Public Enlightenment Campaigns On mentioning
confidence: 99%
“…[1][2][3] Sixteen million young women aged [15][16][17][18][19] give birth annually, including two million in Latin America. 4,5 Ninety-five per cent of births to young women aged [15][16][17][18][19] were in low-and middle-income countries in 2008, 5 and young people aged 15-24 accounted for approximately 60% of all sexually transmitted infections in 2005. 6 In developing regions as a whole, two-thirds of unsafe abortions that occurred in 2004 were among women aged 15-30 and 14% among women under age 20, 7 yet only half of sexually active young women in Latin America who did not wish to become pregnant were using a modern contraceptive method in 2007.…”
mentioning
confidence: 99%
“…15 Research from around the world has found that youth who receive peer education boast improved knowledge, attitudes and behaviours regarding sexual and reproductive health, and that peer educators are crucial to programme success. [16][17][18][19][20][21] Youth who discuss sexual and reproductive health with peers are more likely to display positive health-seeking behaviours than youth who discuss it with adults. Sexually active young people are also far more likely to discuss sexual and reproductive health with peers than adults, 17 and more open to discussing genderrelated issues when presented the topic by peers.…”
mentioning
confidence: 99%
See 1 more Smart Citation